Resorption behaviour of the articular surface dome and functional outcome after open reduction and internal fixation of mandibular condylar head fractures using small-fragment positional screws. Issue 11 (November 2018) - Smolka, Wenko; Cornelius, Carl-Peter; Lechler, Carolin
Abstract: Purpose: The aim of the study was to evaluate the resorption of the mandibular condylar head after open reduction and internal fixation of fractures with small-fragment screws and to evaluate the functional outcome. Patients and method: Forty-eight patients (55 condylar head fractures) underwent surgical treatment. All kinds of complications were recorded. In a subgroup of 20 patients, the average loss of bone height of the condylar head joint surface was gauged by measuring the vertical distances from 3 selected reference points of the fixation hardware to the vertex of the condyle in views of multiplanar radiographs after 6 months. Functional outcome was analysed by Helkimo index score. Results: Complication rates were low. Osteosynthesis loosening occurred in 4 cases. The mean bone resorption along the condylar head joint surface in the subgroup of 20 patients (with 23 joints) was 0.7 mm. Functional outcome was rated as follows: 8 patients - good, 11 patients – slightly impaired, 1 patient - moderately impaired. Conclusion: Open reduction and internal fixation of condylar head fractures with small-fragment screws leads to reliable results in terms of joint surfaces relatively resistant to resorption and function. Low bone resorption on the joint surface of the condylar head can be expected.